Ionizing Electromagnetic Radiation: Its Health Effects and Methods of Prevention - Zainab Jawad Jabber (Universitas Negeri Malang, 2026)
Here we present a review of the biological effects and prevention of ionizing radiation at doses relevant to acute radiation sickness or cancer as well as contemporary shielding methods and International Commission on Radiological Protection (ICRP) guidelines in order to bridge gaps in understanding potential strategies for health protection against ionizing radiation exposure. This review assessed acute and chronic health impacts, synthesized dCCTP-derived ICRP safety regulations for modern shielding materials, evaluated lead compared to lead-free shielding solutions, and identified advancements in radiation risk mitigation strategies. Methods: We implemented a systematic literature search of clinical, material science, and regulatory research published from 2000 to 2023 in peer-reviewed journals with critical thematic analysis. We summarize below important findings pertaining to this chapter: (a) Acute radiation sickness mechanisms involve complex pathways involving mitosis coupled with cellular damage; (b) cancer risks are highly linear with dose and duration of exposure; (c) modern shielding materials in combination provide comparable attenuation efficacy to traditional metals such as lead but greatly reduce environmental toxicity; (d) historical regulations set out by ICRP have changed substantially since the advent of nuclear technologies, likely leading to greater acceptable occupational doses; and (e) recent innovations aimed at reducing long-term risk include improved dosimetric approaches for personal monitoring and biological countermeasures. Overall, these findings highlight the integration of biology with materials and regulatory aspects, which makes radiation protection complicated. The synthesis will provide guidance for future research directions and aid in the development of radiation protection policies intended to minimize the risk workers and the public face when exposed to ionizing radiation across a broad range of situations.